Financial crises,1929 to the present - Hsu, Sara. (Cheltenham Edward Elgar Publishing, 2017)
This fascinating volume offers a comprehensive synthesis of the events, causes and outcomes of the major financial crises from 1929 to the present day. Beginning with an overview of the global financial system, Sara Hsu presents both theoretical and empirical evidence to explain the roots of financial crises and financial instability in general. She then provides a thorough breakdown of a number of major crises of the past century, both in the United States and around the world. Hsu's thorough and ambitious survey begins with the Great Depression of 1929, the first crisis created within the institutions of our current financial system, and moves through the aftermath of the Depression in the 1930s and 1940s, the inter-crisis period of the 1950s through the 1970s, and the emerging market debt default crisis of the 1980s. From there, she tackles major crises in specific countries from the 1990s on, including those in Mexico, Asia (Thailand, Indonesia, South Korea and Malaysia), Russia, Brazil and Argentina, as well as the Great Recession of 2008. The book concludes with a chapter detailing insightful policy recommendations for preventing future crises. Students and professors of economic history, financial and regulatory economics and banking will find this an invaluable resource, both for its comprehensive historical approach and its thoughtful look toward the future of the global economy
Includes bibliographical references (pages 201-234) and index.
Keywords: Financial crises--History--20th century